The Relationship Between Homework Habits and Mathematics Learning Achievement of Upper-Grade Elementary School Students - Rezkya; Muhammad Idris Jafar; Sitti Rahmi (PT. Lontara Digitech Indonesia, 2026)
This study uses a quantitative approach with a correlational research type and symmetrical design aimed at determining the relationship between two or more variables without any effort to influence these variables. In this study, there are two variables, namely homework habits and Mathematics learning achievement. The sample in this study was the upper grades by taking the entire population, namely 40 students, with 22 fourth-grade students, 8 fifth-grade students, and 10 fifth-grade students. Data collection in this study was in the form of questionnaires and documentation. The analysis techniques used in this study were descriptive analysis, which included mean analysis techniques, percentages, and inferential analysis. The results of this study indicate that students’ homework habits and the learning achievement of upper-grade students of SD Inpres 6/80 Kawerang, Bone Regency are in the good category. The conclusion of this study is that there is a significant relationship between students’ homework habits and the mathematics learning achievement of upper-grade students of SD Inpres 6/80 Kawerang, Bone Regency, as evidenced by rcount ≥ rtable (0.98 ≥ 0.31) and a sig. value of 0.000 < 0.05.